2011
DOI: 10.1371/journal.pone.0023873
|View full text |Cite
|
Sign up to set email alerts
|

Visual Working Memory Capacity Does Not Modulate the Feature-Based Information Filtering in Visual Working Memory

Abstract: BackgroundThe limited capacity of visual working memory (VWM) requires us to select the task relevant information and filter out the irrelevant information efficiently. Previous studies showed that the individual differences in VWM capacity dramatically influenced the way we filtered out the distracters displayed in distinct spatial-locations: low-capacity individuals were poorer at filtering them out than the high-capacity ones. However, when the target and distracting information pertain to the same object (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…The current finding of coarse-to-fine processing for high-resolution representations was also supported by the results of our recent behavioral and ERP studies [53], [54], [55], [56], [57]. If coarse-to-fine processing takes place, coarse information can be encoded without accompanying detailed information, but not vice versa.…”
Section: Discussionsupporting
confidence: 86%
“…The current finding of coarse-to-fine processing for high-resolution representations was also supported by the results of our recent behavioral and ERP studies [53], [54], [55], [56], [57]. If coarse-to-fine processing takes place, coarse information can be encoded without accompanying detailed information, but not vice versa.…”
Section: Discussionsupporting
confidence: 86%
“…six in the present study), H is the hit rate or proportion of correct responses when a change is present and F is the false alarm rate or proportion of incorrect responses when no change is present. As with many previous VWM studies, participants were divided into a high-capacity group and a low-capacity group by using a median split on their K c scores (Li, He, Wang, Hu, & Guo, 2017;Owens et al, 2012;Vogel et al, 2005;Weaver, Hickey, & van Zoest, 2017;Zhou et al, 2011).…”
Section: Vwm Capacity Measurement Analysismentioning
confidence: 99%
“…Furthermore, the neural substrate of N270 lies at anterior cingulate cortex (ACC), which fits well with the neural region for conflict processing Zhang et al 2008). Recently, some researchers have successfully adopted the N270 to explore the inner representation issues, such as the representation mechanisms in visual working memory, the number representation, and found that the N270 profiles matched well with the implication of the behavioral performance (e.g., Chen et al 2009;Gao et al 2010;Newman and Connolly 2004;Yin et al 2011;Zhou et al 2011). Here, we asked participants to do different levels of processing for the firstpresented numbers, and then compare the memory representation of the first numbers with the second input, to examine whether the N270 was modulated by the notation types of the second input numbers.…”
Section: Introductionmentioning
confidence: 70%